MiR‐10a and miR‐181c regulate collagen type I generation in hypertrophic scars by targeting PAI‐1 and uPA. Issue 3 (29th December 2014) - Li, Chao; Zhu, Hua-Yu; Bai, Wen-Dong; Su, Lin-Lin; Liu, Jia-Qi; Cai, Wei-Xia; Zhao, Bin; Gao, Jian-Xin; Han, Shi-Chao; Li, Jun; Hu, Da-Hai
Abstract : Urokinase type plasminogen activator (uPA) and plasminogen activator inhibitor‐1 (PAI‐1) have been proposed to play key roles in extracellular matrix (ECM) deposition in hypertrophic scars (HS). Here, we found that in HS fibroblasts (HFs) miR‐181c and miR‐10a were differentially‐expressed and targeted uPA and PAI‐1, respectively. The production of Type 1 collagen (Col1) was inhibited by miR‐181c knockdown or miR‐10a overexpression in HFs, and this resulted in increased levels of metalloproteinase 1 (MMP1). These results suggest that the miR‐181c–uPA and miR‐10a–PAI‐1 regulatory pathways have an integral role in HS pathogenesis. Abstract : uPA and PAI‐1 are aberrantly expressed in hypertrophic scars (HS). uPA is targeted by miR‐181c in hypertrophic scar fibroblasts (HFs). PAI‐1 is targeted by miR‐10a in HFs. There is a reverse correlation of either miR‐181c/uPA or miR‐10a/PAI‐1 within HS. Type 1 collagen and MMP1 are regulated by miR‐181c and miR‐10a in HFs.